1998
DOI: 10.1074/jbc.273.38.24884
|View full text |Cite
|
Sign up to set email alerts
|

CREB and Its Associated Proteins Act as Survival Factors for Human Melanoma Cells

Abstract: cAMP response element-binding protein (CREB) and activating transcription factor 1 (ATF-1), members of the CREB/ATF family, have been implicated in cAMPand calcium-induced transcriptional activation. We have previously demonstrated that quenching of CREBassociated proteins in metastatic melanoma cells by a dominant-negative CREB (KCREB) that is mutated within its DNA-binding domain decreased their radiation resistance, and their tumorigenic and metastatic potential in nude mice. As the induction of apoptosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 38 publications
7
116
0
Order By: Relevance
“…Many oncogenes have been shown to encode proteins that trasmit mitogenic signals upstream of the MAPK pathway (Seger and Krebs, 1995;Sebolt-Leopold, 2000). Phosphorylation of CREB generates signals that inhibit apotosis (Jean et al, 1998;Jean and Bar-Eli, 2000). Control of phosphorylation in gastrointestinal malignancies has recently been reported as an important mechanism for some neoplasia (Saha et al, 2001;Higashi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Many oncogenes have been shown to encode proteins that trasmit mitogenic signals upstream of the MAPK pathway (Seger and Krebs, 1995;Sebolt-Leopold, 2000). Phosphorylation of CREB generates signals that inhibit apotosis (Jean et al, 1998;Jean and Bar-Eli, 2000). Control of phosphorylation in gastrointestinal malignancies has recently been reported as an important mechanism for some neoplasia (Saha et al, 2001;Higashi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence supports the belief that a variety of transcription factors are important in the pathogenesis of melanoma, including activating transcription factor-1 (ATF-1) (Bohm et al, 1995;, cAMP response elementbinding protein (CREB) Jean et al, 1998b;Rutberg et al, 1994;Xie et al, 1997b), transcription factor AP-2 (Huang et al, 1998;Jean et al, 1998a), micropthalmia transcription factor (Mitf) (Goding, 2000;King et al, 1999;Fang and Setaluri, 1999), and nuclear factor-kappa B (NF-kB) . In particular, we have previously demonstrated that the transition of melanoma to the metastatic phenotype is associated with a loss of expression of the transcription factor AP-2 (Bar- Eli, 1997Eli, , 1999).…”
Section: Introductionmentioning
confidence: 99%
“…CREB is also associated with the prevention of apoptosis in melanoma cells, however, the authors of that study were unable to correlate the inhibition of apoptosis with changes in the level of Bcl-2, Bcl-X L , Bad or Bax expression. 105 In addition, p90 Rsk may have anti-apoptotic effects independent of the transcription of anti-apoptotic genes. p90 Rsk has been shown to phosphorylate BAD on serine residue 112.…”
Section: The Ras/raf/mek/erk Signaling Kinase Cascadementioning
confidence: 99%